Role of a cystine-based Gemini surfactant ligand in the synthesis of catalytic active silver nanoparticles - Molina Torres, Maria Andrea (2019)
We report the synthesis in water of colloidal silver nanoparticles (AgNP) using a Gemini lipoamino acid surfactant derived from cysteine as a capping agent. The Gemini surfactant interacts with the metal surface mainly in a monodentate vertical mode through the carboxylate group preserving intact the disulfide bond. These nanoparticles present catalytic activity to the reduction of p-nitrophenol, and the synthesis of AgNP under mild reduction conditions maintaining the seeds size. Also, the Gemini surfactant leads to anisotropic morphologies in the seed-mediated growth of AgNP@citrate seeds aided by the presence of bromide ions.